Reducing creative labour precarity: beyond network connections - Farr-Wharton, B.; Brown, Kerry; Keast, R.; Shymko, Y. (Emerald, 2015)
Purpose – The purpose of this paper is to investigate the impact of organisational business acumen and social network structure on the earnings and labour precarity experienced by creative industry workers. Design/methodology/approach – Results from a survey that collected data from a random sample of 289 creative workers are analysed using structural equation modelling. Mediating effects of social network structure are explored. Findings – Results support the qualitative findings of Crombie and Hagoort (2010) who claim that organisational business acumen is a significant enabler for creative workers. Further, social network structure has a partial mediating effect in mitigating labour precarity. Research limitations/implications – This exploratory study is novel in its use of a quantitative approach to understand the relationship between labour and social network dynamics of the creative industries. For this reason, developed scales, while robust in exploratory and confirmatory factor analysis, warrant further application and maturity. Practical implications – The organisational business acumen of creative workers is found to mitigate labour precarity and increase perceived earnings. Social implications – The results from this study call for policy and management shifts, to focus attention on developing business proficiency of creative workers, in an effort to curb labour precarity in the creative industries, and enhance positive spillovers into other sectors. Originality/value – The paper fills a gap in knowledge regarding the impact of organisational business acumen and social network structure on the pay and working conditions of people working in a sector that is dominated by self-employed and freelance arrangements.